A comprehensive assessment of the state-of-the-art virtual synchronous generator models; Electric Power Systems Research; Vol. 209 - Suvorov A. A. Aleksey Aleksandrovich; Askarov A. B. Alisher Bakhramzhonovich; Kievets A. V. Anton Vladimirovich; Rudnik V. E. Vladimir Evgenevich (2022, 2022)
Title screen